Gender, climate change, and resilient food systems: Lessons from strategic adaptation by smallholder farmers in Cameroon - Nkengla-Asi, Lilian; Babu, Suresh Chandra; Kirscht, Holger; Apfelbacher, Scarlett; Hanna, Rachid; Tegbaru, Amare (International Food Policy Research Institute, 2017)
Climate change has major impacts on the food security and livelihoods of smallholder farmers in Africa south of the Sahara. Vulnerable to the vagaries of weather and to being chronically poor, women farmers are unequally and more negatively affected by climate change and seasonal changes than male farmers. This study aims to understand how men and women in Cameroon’s Southwest region differ in their vulnerability to and their coping strategies for climate change impacts. Data collected through focus group discussions and in-depth interviews from four rural communities in the Southwest region showed that most respondents (both male and female) had observed a change in the climate in the previous 10 years. According to respondents, climate variables such as the timing and length of the rainy season had changed, affecting crop production of both men and women. Women were shown to be more vulnerable than men, as the changes led to a reduction in yields, which affected family well-being. Men and women in the researched communities strive to cope with climate change and related seasonal variations in different ways. Whereas most men tend to move away from the area in a search for paid jobs in the cities, women remain in their own communities and work to diversify their livelihood activities. Other coping strategies for men and women in the research communities include income diversification, planting of early-maturing crops, and use of pest-resistant seeds. Men and women have different experiences and different adaptation strategies to climate change and seasonal variations in weather patterns. Understanding such gender differences could facilitate the development of gender-sensitive policies and programs and could help improve sustainable and more inclusive adaptation strategies.